(untitled) (The Journal of Sindhuli Multiple Campus, 2026)
The world is plagued by critical issues including non-consensual intimacy, sexual coercion, pressure, and certain breaches of body autonomy due to coercion. This is an overly complex issue. A multidisciplinary approach is required to address issues that transcend the scope of individual disciplines. This paper aims to examine the reasons, forms, and effects of nonconsensual intimacy from an interdisciplinary approach. The legal system addresses the issue of pressure as well as the concept of consent. Why is this the case? Non-adherence to due process and the failure to recognize the concept of power imbalance make the legal system unfair to the victim. Sociology delves into the oppression, coercion, and perpetuation of violence and stigmatization faced by the victim due to patriarchal, unequal, and violence-oriented gender constructs. Brutality, intimidation, and stigmatization of the victim are the consequences of the structural violence created by the foundation. In addition to the health consequences of nonconsensual intimacy, the public health system must address the issue of violence in order to address the profound social and health consequences faced by the victim. This paper aims to prove the importance of the use of a holistic conceptual approach to deal with all the effects in a cohesive manner with the help of non-consensual systemic violence. The legal system incorporates aggressive measures, reform policies, and organizational structures of intervention with a focus on behavior and the purposeful addressing of harmed situational status and social system aggression. The sequential approach of rehabilitation to break the stigma of protective dissonance.